From the criminal to the sinthome: Lacan's ethics of psychoanalysis and contemporary life - Bosetti, Luca (2010)
This thesis examines the continuity and the changes in Lacan's elaboration of psychoanalytic ethics. It focuses in particular on the shift from Lacan's classic formulation of psychoanalytic ethics in relation to the criminal figures of Sade and Antigone in Seminar VII, to his later formulation of a psychoanalytic ethics based on a re-elaboration of the concept of symptom - the sinthome - in the 1970s. By illustrating the way in which psychoanalytic ethics is constantly, from Freud to Lacan, defined against a critique of civilization, and by engaging with a number of contemporary clinical readings of Lacan's work, this thesis argues that the development of Lacan's understanding of psychoanalytic ethics should be seen as an attempt to adapt the practice of psychoanalysis to a major change in the structure of contemporary civilization. In this way, this thesis also insists on the importance of maintaining a distinction between Lacan's theory of ethics and, on the other hand, the ethical effects of psychoanalytic practice, and aims to explore the dialogue, the exchanges and the tensions between psychoanalytic practice and contemporary culture.